Four new species of the Oriental genus Elacatophora L. W. Schaufuss (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2020)
Ten hitherto known species of Elacatophora L. W. Schaufuss are distributed in the Malay Peninsula, Borneo and Java. Four newly described species expand the known genus range to Sumatra (Elacatophora jambiana sp. n. and E. kerinciana sp. n.), Thailand (E. thailandiana sp. n.), and north-eastern sub-Himalayan India (E. indica sp. n.).